A STUDY ON REVIEW OF LITERATURE: CONSUMER BUYING BEHAVIOUR TOWARDS E-MOPED (International Journal of Food and Nutritional Sciences, 2022)
Education has been a boon for mankind and yet again we are relying on our educational prowess to fight the evil of environmental change. Though a modest approach but should be a breakthrough if we consistently work towards sustainability. India a developing but critical contributor to global sustainability has set an ambitious program toward a greener future. The electric vehicles (EV) market is growing tremendously all over the world but was lagging behind the much-required impetus in the Indian market. Recent government interventions and policy changes have seen substantial momentum in the EV market in India.